Neuroimmunology of Common Parasitic Infections in Africa - Idro, Richard; Ogwang, Rodney; Barragan, Antonio; Raimondo, Joseph Valentino; Masocha, Willias (Frontiers in Immunology, 2022)
Parasitic infections of the central nervous system are an important cause of morbidity and mortality in Africa. The neurological, cognitive, and psychiatric sequelae of these infections result from a complex interplay between the parasites and the host inflammatory response. Here we review some of the diseases caused by the most common parasitic organisms known to infect the nervous system including Plasmodium falciparum, Toxoplasma gondii, Trypanosoma brucei spp., and Taenia solium species. For each parasite, we describe the geographical distribution, prevalence, life cycle, and typical clinical symptoms of infection and pathogenesis. We pay particular attention to how the parasites are able to infect the brain and the interaction between each organism and the host immune system. We describe how an understanding of these processes may guide optimal diagnostic and therapeutic strategies to treat these disorders. Finally, we highlight current gaps in our understanding of disease pathophysiology and call for enhanced interrogation of these often-neglected disorders of the nervous system.